Drug use in Australian nightlife settings: estimation of prevalence and validity of self‐report. (3rd September 2015) - Miller, Peter; Curtis, Ashlee; Jenkinson, Rebecca; Droste, Nicolas; Bowe, Steven J.; Pennay, Amy
Abstract: Aims: This study aimed to (1) estimate the prevalence of illicit drug use in night‐time entertainment districts across five major cities in Australia; and (2) validate self‐reported drug use using biochemical marker oral swabs. Design: Street intercept surveys and oral drug swabs conducted over a 7‐month period during 2011–12. Setting: The night‐time entertainment districts of three metropolitan cities (Sydney, Melbourne and Perth) and two regional cities (Wollongong and Geelong) in Australia, between the hours of 10 p.m. and 5 a.m. Participants: A total of 7581 individuals agreed to participate in the survey (93% response rate). More than half (62%) the sample was male, with a median age of 22 years (range 18–73). Measurements: Patrons were approached in thoroughfares and while entering and leaving licensed venues. Data collected included demographics and current session alcohol and other substance use. Drug swabs ( n  = 401) were performed with a subsample of participants. Findings: Approximately 9% [95% confidence interval (CI) = 7–12%] of participants self‐reported consumption of illicit or non‐prescribed pharmaceutical drugs prior to interview; of those, 81% identified psychostimulants as the drug used. One in five drug swabs returned a positive result, with psychostimulants the most commonly detected drugs (15%; 95% CI = 12–19%). Kappa statistics indicate agreement between self‐report of any illicit drug and a positive drug swab is in the slight range [κ = 0.12 (95% CI = 0.05–0.20) P  = 0.000]. Conclusions: Self‐report findings suggest drug use in Australian nightlife is common, although still very much a minority past‐time. Drug swabs indicate a higher prevalence of use (20%) than self‐report (9%), which suggests that self‐reported drug use may not be reliable in this context.